2013
DOI: 10.1080/13803395.2012.733682
|View full text |Cite
|
Sign up to set email alerts
|

Development of normative neuropsychological performance in Thailand for the assessment of HIV-associated neurocognitive disorders

Abstract: International studies of HIV-associated neurocognitive disorder (HAND) are needed to determine the viral and host factors associated with cognitive impairment particularly as more than 80% of HIV+ subjects reside in resource-limited settings. Recent diagnostic nomenclature of HAND requires comparison of cognitive performance specifically to local normative data. To evaluate this need for local norms, we compared normative data obtained locally in Thailand to Western norms. The current study examined cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 19 publications
6
31
0
Order By: Relevance
“…The low frequency (<1%) of HIV-infected monocytes in the peripheral 19 blood and the difficulty of obtaining tissue samples present major barriers 20 to elucidating the dynamics of HIV infection in human monocytes. [10] 21 Earlier studies focusing on circulating monocytes revealed genetic patterns 22 distinct from that of T cells, [11][12][13] consistent with the hypothesis of 23 differing viral population dynamics. However, investigation of the role(s) of 24 monocytes in the evolution and spread of HIV-1 has been largely limited to 25 the differentiated macrophage phenotype.…”
supporting
confidence: 63%
“…The low frequency (<1%) of HIV-infected monocytes in the peripheral 19 blood and the difficulty of obtaining tissue samples present major barriers 20 to elucidating the dynamics of HIV infection in human monocytes. [10] 21 Earlier studies focusing on circulating monocytes revealed genetic patterns 22 distinct from that of T cells, [11][12][13] consistent with the hypothesis of 23 differing viral population dynamics. However, investigation of the role(s) of 24 monocytes in the evolution and spread of HIV-1 has been largely limited to 25 the differentiated macrophage phenotype.…”
supporting
confidence: 63%
“…14 We conducted consensus conferences with two of the authors (VV, RP) and a US neurologist to assign HAND diagnoses using 2007 Frascati criteria. 15 We calculated a composite neuropsychological testing score (NPZ- global) as the arithmetic mean of age- and education-adjusted z-scores for performance on individual tests using normative data from over 500 Thai controls 16 .…”
Section: Methodsmentioning
confidence: 99%
“…We utilized an existing normative NP testing database of HIV-uninfected Thai control participants (n= 449) [19]. For the purpose of this study, we utilized only the 251 HIV-uninfected controls in the similar age range as our AHI participants.…”
Section: Methodsmentioning
confidence: 99%